2016
DOI: 10.1039/c5sm01706h
|View full text |Cite
|
Sign up to set email alerts
|

Distinct impacts of substrate elasticity and ligand affinity on traction force evolution

Abstract: Cell adhesion is regulated by the mechanical characteristics of the cell environment. The influences of different parameters of the adhesive substrates are convoluted in the cell response leading to questions on the underlying mechanisms, like biochemical signaling on the level of adhesion molecules, or viscoelastic properties of substrates and cell. By a time-resolved analysis of traction force generation during early cell adhesion, we wanted to elucidate the contributions of substrate mechanics to the adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 56 publications
3
19
0
Order By: Relevance
“…The expression of adhesion markers, ITGB1, CADH1, which regulate adhesion of cells to the substrate and neighbouring cells was gradually enhanced by substrate stiffening (Figure 4). This is probably related to higher spreading which elevates the number of cell-substrate adhesion bonds, and increased cell traction forces that together enhance cell adhesion ability to the substrate [52,53]. Additionally cell-cell tension forces is proportional to cell-ECM traction forces [54].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of adhesion markers, ITGB1, CADH1, which regulate adhesion of cells to the substrate and neighbouring cells was gradually enhanced by substrate stiffening (Figure 4). This is probably related to higher spreading which elevates the number of cell-substrate adhesion bonds, and increased cell traction forces that together enhance cell adhesion ability to the substrate [52,53]. Additionally cell-cell tension forces is proportional to cell-ECM traction forces [54].…”
Section: Discussionmentioning
confidence: 99%
“…Nuclei were labelled with NucBlue Live reagent (R37605, Thermo Fisher Scientific) and blebbistatin (B0560; Sigma) treatment (10μM, 60min) was used as a control of relaxed cellular traction forces. Image stacks before and after cell dissociation were processed in Fiji using the StackReg plugin 54 and bead displacements due to cell tractions and cell tractions were calculated with a previously published unconstrained Fourier-transform traction cytometry method 55 . From the displacement field and traction force, the strain energy has been calculated.…”
Section: Traction Force Microscopy (Tfm)mentioning
confidence: 99%
“…Ligand density acts independently of matrix stiffness to determine the maximum forces generated by cells during adhesion. 84 The way in which the ligands are anchored in the ECM can also modulate cell expression. A 2.5 fold difference in collagen anchoring density was shown to determine stem cell fate.…”
Section: Cell Recognition Of Collagenmentioning
confidence: 99%
“…It has been shown that both high substrate elasticity and high ligand affinity increase traction forces exerted by cells and raise the maximum traction force which can be exerted. 84 As integrin bonding is mediated by mechanosensing and ligand density, biological response to scaffolds is altered. 21 Thus, collagen scaffold cross-linking can direct biological responses, such as the differentiation of mesenchymal stem cells.…”
Section: Harnessing Collagen's Potentialmentioning
confidence: 99%